1998
DOI: 10.1007/bf03401914
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholic Acid May Inhibit Deoxycholic Acid-Induced Apoptosis by Modulating Mitochondrial Transmembrane Potential and Reactive Oxygen Species Production

Abstract: Background: The hydrophilic bile salt ursodeoxycholate (UDCA) inhibits injury by hydrophobic bile acids and is used to treat cholestatic liver diseases. Interestingly, hepatocyte cell death from bile acid-induced toxicity occurs more frequently from apoptosis than from necrosis. However, both processes appear to involve the mitochondrial membrane permeability transition (MPT). In this study, we determined the inhibitory effect of UDCA on deoxycholic acid (DCA)-induced MPT in isolated mitochondria by measuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
252
0
6

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 281 publications
(271 citation statements)
references
References 46 publications
13
252
0
6
Order By: Relevance
“…[107][108][109] UDCA treatment dilutes the concentration of DCA, and is thought to modulate the membrane and inflammatory effects of secondary bile acids on the colonic mucosa by increasing the hydrophilicity of the colonic bile acid milieu, and suppressing cell-signaling pathways activated by DCA. 110,111 Problematically, bile acid 7a-dehydroxylating bacteria, including Clostridium scindens and C. hiranonas are capable of converting UDCA to LCA through bile acid 7b-dehydroxylation. 8 Studies have shown that LCA is toxic, and causes DNA damage in bacteria 112 and colonocytes.…”
Section: Inactivation Of Ursodeoxycholic Acid By 7b-dehydroxylationmentioning
confidence: 99%
“…[107][108][109] UDCA treatment dilutes the concentration of DCA, and is thought to modulate the membrane and inflammatory effects of secondary bile acids on the colonic mucosa by increasing the hydrophilicity of the colonic bile acid milieu, and suppressing cell-signaling pathways activated by DCA. 110,111 Problematically, bile acid 7a-dehydroxylating bacteria, including Clostridium scindens and C. hiranonas are capable of converting UDCA to LCA through bile acid 7b-dehydroxylation. 8 Studies have shown that LCA is toxic, and causes DNA damage in bacteria 112 and colonocytes.…”
Section: Inactivation Of Ursodeoxycholic Acid By 7b-dehydroxylationmentioning
confidence: 99%
“…11 In fact, UDCA appears to regulate apoptosis in both hepatic and nonhepatic cells by preventing mitochondrial depolarization and reactive oxygen species production. 10,13 Interestingly, the ability of UDCA to inhibit apoptosis appears to be independent of the inducing agent and its pathway, suggesting a common antiapoptotic mechanism(s). In particular, while the pathway to execution may be more direct with DCA, the apoptosis from TGF-b1 and okadaic acid are equally sensitive to the inhibitory effects of UDCA.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo DCA feeding was associated with a 4.5-fold increase in mitochondrial-associated Bax protein levels, while combination feeding with UDCA significantly inhibited these changes. 13 Like Bcl-2, UDCA appears to modulate Bax-induced events at several levels, including prevention of Bax redistribution, inhibition of cytochrome c release, and modulation of cytochrome cmediated downstream events such as DEVD-specific caspase activity and PARP cleavage. It remains to be determined whether other factors, such as Bid-induced conformational change of Bax and cytochrome c release, 64 are in some way modulated by UDCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Extracts were prepared from nuclei and highly purified mitochondria isolated from rat liver, and the authenticity and purity of the extracts established by Western blot, enzymatic activity and electron microscopy. [28][29][30] Using this PCR-independent bacterial read-out system and extracts derived from rat liver, we have observed a chimeraplast-specific and mitochondrial protein extract dose-dependent growth of dual resistant colonies, ranging from 0.003 ± 0.002% to 0.05 ± 0.002%. This rate of repair in vitro did not differ significantly from that observed in parallel reactions using rat liver nuclear extract.…”
mentioning
confidence: 99%